Comparison of non-Ohmic accelerated ageing of the ZnO- and SnO2-based voltage dependent resistors - Ramirez, M. A. [UNESP]; Cilense, M. [UNESP]; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Iop Publishing Ltd, 2009)
The ageing of non-Ohmic features of ZnO and SnO2-based polycrystalline semiconductors under fixed dc bias voltage at different temperatures (or thermal steady states) was comparatively investigated in this work. The ageing under these conditions was evaluated by monitoring the leakage current as a function of time (I-1 versus t) and by the calculation of the potential barrier height before and after degradation or ageing cycle, for two specific compositions. The results showed that the non-Ohmic features of the ZnO-based compositions studied here were irreversibly aged when the system reaches temperatures around 90 degrees C with the thermal runaway mechanism being activated around 110 degrees C. on the other hand, the SnO2-based composition shows stable and reversible non-Ohmic behaviour during application of an equivalent stress voltage cycle (reversible features). It was also observed that the thermal runaway process starts at a higher temperature, i.e. 200 degrees C, which is comparatively higher than in the ZnO traditional system (about 110 degrees C).